Analysis The Influence of Prices and Features of Honda Vario 125 CBS 2020 on Purchase Decisions for Candidate Consumers in The Tangerang City Region - Susanto, Renaldy; Novitasari, Dewiana; Yuwono, Teguh; Asbari, Masduki (AGUSPATI Research Institute, 2020)
This study aims to determine the purchase decision for the Honda Vario 125 CBS 2020 in the Tangerang City area. The level of congestion in big cities continues to increase so that many people decide to work using motorbikes because it speeds up time compared to cars and certainly makes it cost-effective. The research method used methods probability sampling with a population of 52 with accidental sampling technique. Calculations using the Slovin formula with a sample size of 46.01 people, then rounded up to 50 samples. The test results show that 77% of customer satisfaction can be influenced by the product quality and service quality, while the remaining 23% is influenced by other variables that are not explained in the linear regression model such as price, promotion, etc. PT. Wahana Artha Ritelindo is advised to maintain service stability because if the services provided decline, consumers will switch to competitors. The results of this study indicate that there is a significant influence between the Honda Vario 125 CBS 2020 product on the price effect at PT. Wahana Honda Jatiuwung, as evidenced by the value of tcount = 6.294> ttable= 0.2787; sig 0.000 <0.05 and the regression coefficient (b) is 0.689. There is a significant influence between the influence of features on PT. Wahana Artha Ritelindo, as evidenced by the value of tcount= 6.295> ttable= 0.2787; sig = 0.000 <0.05 and the regression coefficient (b) is 0.678. There is a significant influence on the effect of purchasing decisions at PT. Wahana Artha Ritelindo, evidenced by the value of Fcount = 8.160> Ftable= 0.2787; sig = 0.000 <0.05 and the value of the regression coefficient (b1) is 0.372; the value of the regression coefficient (b2) is 0.630.